Fundamentals of demography - Majumdar, P.K (Jaipur, 2010)
Written in a straightforward and lucid style, this book - based on academic scholarship in India - is an ideal textbook for undergraduate and graduate students, as well as amateur readers taking their first course in demography. While providing sufficient depth and analytical rigor for use in graduate courses on population dynamics, the book will help students understand and comprehend the basic tenets of demography with self-explanatory examples and illustrations. It provides a solid introduction to all the hallmark subjects, methodologies, and debates covered in standard courses on population. Featuring a cross-disciplinary approach to demography, using global examples with depth and clarity, it is sociologically oriented, although economics, political science, geography, history, and the other social sciences are also used to inform the materials. Although the emphasis is on demography, the book recognizes that, at the individual level, population change is related to private decisions, especially in relation to fertility, mortality, and migration. Changes in population size have an important effect on the environmental and related challenges facing the world. Therefore, attention is paid to the broad implications of population growth.
Keywords: Demography